Trypsin-encoding PRSS1-PRSS2 variations influence the risk of asparaginase-associated pancreatitis in children with acute lymphoblastic leukemia: a Ponte di Legno toxicity working group report - Wolthers, Benjamin O; Frandsen, Thomas L; Patel, Chirag J; Abaji, Rachid; Attarbaschi, Andishe; Barzilai, Shlomit; Colombini, Antonella; Escherich, Gabriele; Grosjean, Marie; Krajinovic, Maja; Larsen, Eric; Liang, Der-Cherng; et al. (Haematologica, 2019)
Asparaginase-associated pancreatitis is a life-threatening toxicity to childhood acute lymphoblastic leukemia treatment. To elucidate genetic predisposition and asparaginase-associated pancreatitis pathogenesis, ten trial groups contributed remission samples from patients aged 1.0-17.9 years treated for acute lymphoblastic leukemia between 2000 and 2016. Cases (n=244) were defined by the presence of at least two of the following criteria: (i) abdominal pain; (ii) levels of pancreatic enzymes ≥3 × upper normal limit; and (iii) imaging compatible with pancreatitis. Controls (n=1320) completed intended asparaginase therapy, with 78% receiving ≥8 injections of pegylated-asparaginase, without developing asparaginase-associated pancreatitis. rs62228256 on 20q13.2 showed the strongest association with the development of asparaginase-associated pancreatitis (odds ratio=3.75; P=5.2×10-8). Moreover, rs13228878 (OR=0.61; P=7.1×10-6) and rs10273639 (OR=0.62; P=1.1×10-5) on 7q34 showed significant association with the risk of asparaginase-associated pancreatitis. A Dana Farber Cancer Institute ALL Consortium cohort consisting of patients treated on protocols between 1987 and 2004 (controls=285, cases=33), and the Children's Oncology Group AALL0232 cohort (controls=2653, cases=76) were available as replication cohorts for the 20q13.2 and 7q34 variants, respectively. While rs62228256 was not validated as a risk factor (P=0.77), both rs13228878 (P=0.03) and rs10273639 (P=0.04) were. rs13228878 and rs10273639 are in high linkage disequilibrium (r2=0.94) and associated with elevated expression of the PRSS1 gene, which encodes for trypsinogen, and are known risk variants for alcohol-associated and sporadic pancreatitis in adults. Intra-pancreatic trypsinogen cleavage to proteolytic trypsin induces autodigestion and pancreatitis. In conclusion, this study finds a shared genetic predisposition between asparaginase-associated pancreatitis and non-asparaginase-associated pancreatitis, and targeting the trypsinogen activation pathway may enable identification of effective interventions for asparaginase-associated pancreatitis.
Keywords: Genetic Predisposition to Disease; alely; Pancreatitis; genotyp; jednonukleotidový polymorfismus; Alleles; asparaginasa; kojenec; Genotype; mladiství; akutní lymfatická leukemie; mužské pohlaví; Asparaginase; genetická variace; Infant; Trypsinogen; Polyethylene Glycols; fenotyp; Antineoplastic Agents; dítě; polyethylenglykoly; Child; trypsin; Genetic Variation; Models, Biological; Child, Preschool; Trypsin; Phenotype; ženské pohlaví; protinádorové látky; genetické asociační studie; Humans; předškolní dítě; biologické modely; trypsinogen; Genetic Association Studies; genetická predispozice k nemoci; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Female; pankreatitida; Adolescent; lidé; Male; Polymorphism, Single Nucleotide